Optimisation of the cultured ELISpot/Fluorospot technique for the selective investigation of SARS-CoV-2 reactive central memory T cells - Jerome, Jack R.; Wilson, Kirsty L.; Fialho, Joshuah; Goodchild, Georgia; Prakash, Monica D.; McLeod, Charlie; Richmond, Peter C.; Apostolopoulos, Vasso; Flanagan, Katie L.; Plebanski, Magdalena (Frontiers in Immunology, 2025)
IntroductionThis study presents an optimised cultured ELISpot protocol for detecting central memory T-cell interferon gamma (IFNγ) responses against SARS-CoV-2 peptides following an initial priming with either peptides, or whole spike protein.MethodsKey variations optimised include the culture length, timing of exogenous survival signals (IL-2), and endpoint analysis modality and cell density to enhance assay sensitivity without compromising specificity for central memory T-cell IFNγ recall responses to cognate antigen.ResultsWe noted a culture duration of 10 days, combined with a delayed IL-2 administration on day 5 to enhance assay sensitivity while maintaining response specificity towards cognate antigen when compared with shorter culture periods or earlier exogenous survival signal provision. With regards to lower-frequency T-cell interactions, as we observed with our donor SARS-CoV-2 epitope responses, our findings suggest Fluorospot to be preferable to the chromogenic ELISpot modality, and an immediate cell washing after culture collection to better facilitate cognate antigen responses. Fluorospot enabled a higher cell density while minimising the generation of visual artefacts, meanwhile immediate cell washing was critical for improving endpoint assay sensitivity. CCR7+ cell depletion was used to demonstrate our optimised protocol to selectively demonstrate central memory T-cell responses. Lastly, we provide evidence for the capacity of our assay to delineate individual responding peptides following peptide pool priming, and to explore cross-reactivity between viral variant peptides.ConclusionThis work advances the methodology for investigating T-cell immunity, particularly in the context of SARS-CoV-2, and emphasises the balance between enhancing specific cognate central memory responses while limiting non-specific activation.